Graphene acoustic plasmon resonator for ultrasensitive infrared spectroscopy. Issue 4 (April 2019) - Lee, In-Ho; Yoo, Daehan; Avouris, Phaedon; Low, Tony; Oh, Sang-Hyun
Abstract One of the fundamental hurdles in plasmonics is the trade-off between electromagnetic field confinement and the coupling efficiency with free-space light, a consequence of the large momentum mismatch between the excitation source and plasmonic modes. Acoustic plasmons in graphene, in particular, have an extreme level of field confinement, as well as an extreme momentum mismatch. Here, we show that this fundamental compromise can be overcome and demonstrate a graphene acoustic plasmon resonator with nearly perfect absorption (94%) of incident mid-infrared light. This high efficiency is achieved by utilizing a two-stage coupling scheme: free-space light coupled to conventional graphene plasmons, which then couple to ultraconfined acoustic plasmons. To realize this scheme, we transfer unpatterned large-area graphene onto template-stripped ultraflat metal ribbons. A monolithically integrated optical spacer and a reflector further boost the enhancement. We show that graphene acoustic plasmons allow ultrasensitive measurements of absorption bands and surface phonon modes in ångström-thick protein and SiO2 layers, respectively. Our acoustic plasmon resonator platform is scalable and can harness the ultimate level of light–matter interactions for potential applications including spectroscopy, sensing, metasurfaces and optoelectronics. The momentum mismatch between far-field light and acoustic graphene plasmons can be largely overcome by a two-stage coupling scheme for sensitive protein detection in sub-10-nm films.